PROBLEMATIKA BAHASA INDONESIA KEKINIAN: SEBUAH ANALISIS KESALAHAN BERBAHASA INDONESIA RAGAM TULISAN - NFN Akmaluddin (MABASAN, 2016)
Indonesian language has special functions among the Indonesian nation and national life that are Bahasa Indonesia as a national and nation language. On the basis of that functions, Indonesia language is used in official documents in some countries. The language forms shall be used in making official documents are the standardized Indonesia language. As a national language, Indonesian language is used by any levels of community in Indonesia. However, the both functions are not well applied, therefore it creates some Indonesia language problems. Some problems meant are the mistakes in using Indonesian language, either spoken or written. The problems discussed in this research are (1) some of nowadays Indonesian language problems and their solutions, (2) Factors causing the use of Indonesian language in a variety of life usages. The data are collected through observation and documentation. The data are then analyzed by using inductive data analysis. The results of the analysis show that (1) Indonesia language nowadays has some problems in some linguistics features. (2) The mistakes in using Indonesian language are caused by some factors.